(untitled) (Innovative Technologica: Methodical Research Journal, 2021)
The article considers about theoretical background of functional semantic field of words expressing color and image in literature. There are discussed about some opinions, viewpoints of researchers about the lexical-semantic field of “Color” and generalized as well.